If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13q + 91 + -13q = 0 Reorder the terms: 91 + 13q + -13q = 0 Combine like terms: 13q + -13q = 0 91 + 0 = 0 91 = 0 Solving 91 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 8x^2-15x=0 | | -18=14y+10 | | x^4-12x^2+27=0 | | 3.65+e=24.81 | | 8(3x-4)=(9x+3)+7 | | Z-17.2=-47.62 | | 0.03x-0.6=0.75 | | 5.7=9+p | | .7x=1.05 | | 4x*2+11x+6=0 | | 3-2(y-1)=2+4y | | 4x-34=7x+x-14 | | x+(x+6)=54 | | -6b+7+4b=-3b+12 | | x(x+6)=54 | | 2(4)-3(-4)+1=4+25 | | 4=6x | | 5y+3(y-6)=4(y+1)-3 | | 2(-4)-3(4)+1=-4+25 | | 0.5(6x-10)=0.2(25x-15) | | 2z+13-4z=9 | | 5r+6=9-4r | | 2(-3)+3(3)-(-3)=2(-3)-(-3)+9 | | 2x^2+2x-13=0 | | 2(7x+5)+2=14x+12 | | T-6.8=13.9 | | 2x+3(-x)-x=2x-x+9 | | 3p-2=6+4p | | 10-12X+3=-47 | | 9x+6=9(x+3) | | 2(-x)-3x+1=x+25 | | 5m-19=-27+7m |